Economic impacts of electricity transmission and distribution losses in Pakistan: A dynamic inoperability input–output analysis - Ayesha Hidayat Ullah; Yousaf Ali; Muhammad Sabir (Utilities Policy, 2026)

Honeybee venom modulates antioxidant gene expression and tissue regeneration in a rat model of staphylococcus aureus - infected skin wounds - Sabir Ahmed Smael; Treefa Farouq Ismail; Banaz Sdiq Abdullah; Rebwar Muhammad Hamasalih; Esmat Khaleqsefat; Azheen Subhi Abdulrahman; Ramyar Hassan Mahmud; Abubakr Mohammed Amin; Rozi Braim Abdalrahman; Harem Khdir Awla (Molecular Biology Reports, 2026)

Upregulation and diagnostic potential of Interleukin-36 cytokine isoforms in dilated cardiomyopathy: evidence from human and murine models - Alishba Kainat; Mubeen Tabish Nasim; Fazlul Aziz Mian; Syed Muhammad Nurulain; Hassaan Mehboob Awan; Tahir Iqbal; Sabir Hussain (Molecular Biology Reports, 2026)

Alternaria alternata: Mechanism of pathogenicity, host-interactions, and translational applications of pathogenicity research - Muhammad Sabir; Mansoor Hayat; Hasham Ahmad; Imdad Ullah; Zainab Shahbaz; Mobeen Abbas; Zhanbin Wang (Physiological and Molecular Plant Pathology, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Comparative identification of abiotic stress-responsive differentially expressed genes in chickpea using unsupervised machine learning, and traditional meta-analysis - Mohammad Shafiq; Rimshah Sabir; Yossma Waheed; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Genes & Genomics, 2026)

AI-Enabled Digitalization and Environmental Practices in Municipal Waste Management: Pathways to Climate Sustainability in Pakistan - Muhammad Ahsan Iqbal; Asifa Muhammad Sabir; Kundan Kumar; Md Mahfujul Islam (Environmental Management, 2026)
Rapid urbanization and the intensifying pressures of climate change have elevated solid waste management (SWM) as a critical public service challenge. Evidence on the joint mediating effects of digital transformation and environmental governance between municipal SWM and climate sustainability remains questionable. This study examines the role of SWM in promoting climate sustainability by evaluating environmental management practices and AI-enabled digitalization. Data were collected from 406 employees across seven Water and Sanitation Service Companies (WSSCs) in Khyber Pakhtunkhwa, Pakistan, using a cross-sectional survey with a structured and validated instrument. The analytical approach involved Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with bootstrapped mediation analysis (5000 resamples), executed in SPSS and AMOS software. The study measured waste management effectiveness, environmental practices, AI-enabled digital systems, and sustainability outcomes across economic–environmental–social nexus. Findings reveal a significant positive relationship between effective SWM and climate sustainability (β = 0.41, p < 0.001). Environmental practices including regulatory compliance, pollution control, and workforce training along with AI-driven digital capabilities including real-time tracking, route optimization, electronic service reporting, and data dashboards play a strong mediating role (indirect effects: ENV = 0.13; DIG = 0.12; joint = 0.21). The results suggest that municipal waste systems achieve greater climate benefits when routine operations are supported by integrated environmental management and smart digital technologies. The study contributes to the research on sustainable models, circular economy, and smart urban governance, offering policy guidance for municipal authorities in Pakistan, through AI-enabled tools and solutions, environmental governance practices, and SDG-aligned incentives.

Elevated interleukin-36γ and gene polymorphisms implicate novel risk in essential hypertension - Alishba Kainat; Fazlul Aziz Mian; Muhammad Asif Nawaz Khan; Mubeen Tabish Nasim; Syed Muhammad Nurulain; Nazia Bibi; Syed Tahir Abbas Shah; Muhammad Jadoon Khan; Sabir Hussain (Immunogenetics, 2026)

Nanoparticles in potato disease management: Applications, mechanisms, and future perspectives for sustainable crop production - Aneeza Ishfaq; Ishrat Bano; Irfan Haidri; Muhammad Shahid; Muhammad Sohail Akram; Muhammad Khubeb Ashfaq; Sabir Hussain; Tanvir Shahzad; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Theoretical Investigation of Optoelectronic and Photophysical Properties in the Carbazole-based Molecules via DFT and TD-DFT Methodology - Muhammad Zohaib Sabir; Sania Ismaeel; Yasir Ali; Aneeqa Kanwal; Umme Habibah Siddiqua (Journal of Fluorescence, 2026)

Therapeutic targeting of COX-2 in head and neck cancer: Mechanistic and clinical perspectives - Reena Gupta; Bilal Khaleel Midhin; Sabir Ali Siddiqui; Mohammad Abohassan; Pareshkumar N. Patel; Gunjan Singh; Vimal Arora; Priya Priyadarshini Nayak; Muhammad Shahid Iqbal; Zainb A. Taleb (DARU Journal of Pharmaceutical Sciences, 2026)

Enhancing Soil and Atmospheric Carbon Regulation Through Bombax Ceiba-Based Agroforestry in Drylands - Ghulam Yasin; Muhammad Talha Bin Yousaf; Muhammad Atif Latif; Muhammad Azeem Sabir; Muhammad Azeem Akhter; Shafeeq Ur Rahman; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

The impact of acute normovolemic hemodilution on blood transfusions in cardiac surgery: a GRADE-assessed systematic review and meta-analysis of 30 randomized controlled trials with trial sequential analysis - Umama Alam; Shree Rath; Muhammad Ansab; Fazia Khattak; Hafiza Tooba Siddiqui; Muhammad Burhan; Abdul Moiz; Vishma Sabir; Zarar Ahmad Khan Afridi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Rethinking lice management at the human–animal interface: challenges, green alternatives, and the road ahead - Rimsha Jamil; Muhammad Imran; Muhammad Adnan Sabir Mughal; Rao Zahid Abbas; Muhammad Umar Ijaz; Muhammad Kasib Khan; Asghar Abbas; Farhan Ahmad Atif; Sultan Ali (International Journal of Tropical Insect Science, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Susceptibility of two super elite basmati rice varieties cultivated in Pakistan to Whitebacked Planthopper (WBPH) Sogatella furcifera Horváth (Hemiptera: Delphacidae); A life–table bioassay - Muhammad Rizwan; Misbah Rizwan; Arshed Makhdoom Sabir; Muhammad Tahir; Bilal Atta; Tahir Hussain Awan (International Journal of Tropical Insect Science, 2026)

Potential Application of NADPH-Dependent FMN Reductase-Harboring Delftia Acidovorans in Laboratory-Scale Textile Wastewater Treatment and Re-Use - Awais Maqsood; Syeda Khola Tazeen; Sabir Hussain; Faisal Mahmood; Sher Muhammad; Muhammad Shafiq Shahid; Faizah Amer Altihani; Mohamed Hashem; Danish Riaz; Irfan Manzoor; Muhammad Shahid (Water, Air, & Soil Pollution, 2026)

Gypsum and Manure Impacts on Contrasting Textured Saline-Sodic Soils and Greenhouse Gas Emissions - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Muhammad Sabir; Aftab Jamal; Ayesha Abdul Qadir; Bryan G. Hopkins; Muhammad Nadeem Ashraf (Journal of Soil Science and Plant Nutrition, 2026)

Ligand modelling of Trachyspermum ammi phytocompounds for Aeromonas hydrophila cell wall synthesis enzyme in Labeo rohita - Muhammad Burhan Sabir; Aqeela Ashraf; Rashid Saif; Malaika Saeed; Muhammad Osama Zafar (Natural Product Research, 2026)

Apocynin Loaded pH-Sensitive Nanoparticles Based Transdermal Hydrogel: an Innovative Therapeutic Approach against Rheumatoid Arthritis - Raskha Akbar; Dildar Khan; Muhammad Bilal Sabir; Irfa Basharat Rajput; Mona Al Hamod; Asim. ur. Rehman; Naz Dilawar; Shefaat Ullah Shah; Sakina Niyazi; Abdullah R. Alanzi; Hattan A. Alharbi; Kifayat Ullah Shah (Journal of Pharmaceutical Innovation, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Cardiometabolic Dysregulation and PON1 Genetic Susceptibility in Chronic E-waste Recyclers Exposed to Potentially Toxic Elements - Aneela Shoukat; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Sabir Hussain; Sosan Andleeb Khan; Sajid Mehmood; Sadia Asmat; Saqlain Raza; Syed Tahir Abbas Shah (Cardiovascular Toxicology, 2026)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Femtosecond transient absorption spectroscopy investigation on Cu-MOF/g-C3N4 S-scheme heterojunction for photocatalytic CO2 reduction - Muhammad Sabir; Guogen Qiu; Songyu Yang; Muhammad Tahir; Jianjun Zhang; Mahmoud Sayed (Journal of Environmental Chemical Engineering, 2025)

Solid phase microextraction of chlorpyrifos residues in food samples using polyacrylamide@MOF/MXene composite - Sumaira Sabir; Nadeem Raza; Muhammad Hayat; Suryyia Manzoor; Faryal Aftab; Lilia Basilio de Caland; Muhammad Imran Khan; Ahmed Yar; Faisal K. Algethami; Mostafa E. Salem; Anis Ahmad Chaudhary; Muhammad Naeem Ashiq (Food Chemistry, 2025)

Investigation of N-desmethyl-acetamiprid-induced neurotransmitter disturbances in cerebrospinal fluid from leukemia patients - Mengya Si; Muhammad Nadeem Khan; Hazrat Bilal; Muhammad Shafiq; Sabir Khan; Xiaoling Guo; Meimei Wang; Jilong Wu; Wang Zhen; Fen Yao; Adela Jing Li; Xiaoyang Jiao (Environmental Toxicology and Pharmacology, 2025)

Collateral damage of neonicotinoid insecticides: Unintended effects on gut microbiota of non-target organisms - Muhammad Nadeem Khan; Hazrat Bilal; Sabir Khan; Muhammad Shafiq; Xiaoyang Jiao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Green Synthesis, Characterization, and Effect of Zinc Oxide Nanoparticles on Wheat (Triticum Aestivum L.) Under Cadmium Stress - Aqsa Khan; Samina Jam Nazeer Ahmad; Muhammad Jafir; Adeel Ahmad; Muhammad Irfan; Muhammad Qasim; Jam Nazeer Ahmad; Muhammad Azeem Sabir; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Harnessing metal-organic frameworks (MOFs) in agriculture: Mechanisms and application strategies for management of plant diseases - Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Yumna Rasheed; Faizah Amer Altihani; Mohamed Hashem; Faisal Mahmood (Physiological and Molecular Plant Pathology, 2025)

Prediction of water status during freeze drying with genetic and whale algorithms of machine learning - Shoaib Younas; Muhammad Ahmad; Ukasha Arqam; Muhammad Sajid Manzoor; Xin Wang; Weijie Li; Caiyun Liu; Zeshan Ali; Muhammad Azeem Sabir; Muhammad Imran (International Journal of Refrigeration, 2025)

Uncovering the oxidative stress and hematological consequences of chronic cobalt exposure on atherosclerosis - Rashad Ibragimov; Rovshan Khalilov; Fidan Nuriyeva; Ilgiz Gareev; Ozal Beylerli; Sergey Roumiantsev; Muhammad Zafar; Deema Kamal Sabir; Salman Majeed; Muhammad Rizwan Khan; Aleena Gul; Jonida Biturku (BioMetals, 2025)

Functionalized carbon nanotubes interconnected with metal-organic frameworks for in-situ solar-driven evaporation and salt recovery from seawater - Muhammad Sohail Asghar; Muhammad Sultan Irshad; Naila Arshad; Maryam Al Huwayz; Muneerah Alomar; Ghazala Maqsood; Muhammad Atif Ali; Uzma Ghanzanfar; Muhammad Sabir; Jinhua Li; Van-Duong Dao; Nang Xuan Ho; et al. (Water Research, 2025)

UV radiation-induced degradation of moxifloxacin: toxicity evaluation and conditions optimization - Muhammad Imran Kanjal; Majid Muneer; Saif Ullah; Saira Sabir; Reguia Boudraa; Abdeltif Amrane; Lotfi Mouni (Euro-Mediterranean Journal for Environmental Integration, 2025)

Phthalate ester contamination in groundwater at the Himalayan-Potohar Interface: health risks in Rawalpindi, Pakistan - Hidayat Ullah; Bakht Rawan; Marwan Ullah; Muhammad Ibrar Shinwari; Thiago Machado da Silva Acioly; Patricio De los Rios-Escalante; Fedlu Kedir Sabir; Muhammad Ilyas (Environmental Monitoring and Assessment, 2025)

Quantum Chemical Insights into Metal-Ion Enhanced NLO Response of a Fluorescent Probe for Advanced Sensing Application - Asad Ullah; Muhammad Arif Ali; Sabir Ali Siddique; Muhammad Ibrahim; Hong Liang Xu; Abdul Rauf; Amal M. Al-Mohaimeed; Wedad A. Al-onazi; Muhammad Arshad (Journal of Fluorescence, 2025)

Interactive Effects of Biochar Rates and Elevated Temperature on Organic Matter Cycling and Extracellular Enzyme Activity in a Sandy Loam Aridisol - Rummana Basit Mir; Muhammad Sanaullah; Faisal Mahmood; Sabir Hussain; Muhammad Hussnain Siddique; Hayssam M. Ali; Xingliang Xu; Afzal Ahmed; Umme-e-Aiman Fiaz; Tanvir Shahzad (Journal of Soil Science and Plant Nutrition, 2025)

Differential responses of leguminous tree species to drought stress: implications for agroforestry and restoration in arid and semi-arid climates - Muhammad Madnee; Tanveer Hussain; Muhammad Azeem Sabir; Muhammad Abid; Muneeb Khalid; Hussain Ahmad Makki; Sajjad Ali; Nugraha Akbar Nurrochmat (Agroforestry Systems, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

The influence of renewable energy, humanistic culture, and green knowledge on corporate social responsibility and corporate environmental performance - Muhammad Farhan Basheer; Saira Ghulam Hassan; Afshan Ali; Saeed Ahmad Sabir; Waeibrorheem Waemustafa (Clean Technologies and Environmental Policy, 2025)

Prevalence and herd-level risk factors associated with Brucella infection in smallholders keeping large ruminants - Abrar Hussain; Sabir Hussain; Mamoona Chaudhry; Muhammad Asif Ali; Ibrahim Elsohaby; Ubaid-ur-Rehman Zia; Olivier Sparagano (Research in Veterinary Science, 2025)

Enhancement of Antioxidants’ Enzymatic Activity in the Wheat Crop by Shewanela sp. Mediated Zinc Oxide Nanoparticles Against Heavy Metals Contaminated Wastewater - Irfan Haidri; Aneeza Ishfaq; Muhammad Shahid; Sabir Hussain; Tanvir Shahzad; Usman Shafqat; Sadia Mustafa; Faisal Mahmood (Journal of Soil Science and Plant Nutrition, 2024)

Intercalation of GO-Ag nanoparticles in cellulose acetate nanofiltration mixed matrix membrane for efficient removal of chromium and cobalt ions from wastewater - Muhammad Hamad Zeeshan; Umm E. Ruman; Muhammad Shafiq; Sharjeel Waqas; Aneela Sabir (Journal of Environmental Chemical Engineering, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Synthesis, Characterization, Photocatalytic and Antimicrobial Potential of Pr2O3/ZnO/gC3N4 Nanocomposite - Kiran Sabir Ali; Kausar Hussain Shah; Hafiz Muhammad Asif; Muhammad Ali Khan; Shabbir Hussain; Muhammad Tariq (International Journal of Environmental Research, 2024)

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Differential involvement of PEBP genes in early flowering of Peucedanum praeruptorum Dunn - Cheng Song; Wenwu Zhang; Muhammad Aamir Manzoor; Irfan Ali Sabir; Haoyu Pan; Luxi Zhang; Yingyu Zhang (Postharvest Biology and Technology, 2024)

Exposure to heavy metals, antioxidant status, and the interaction of single nucleotide polymorphisms in the genes CAT rs7943316, GSTP1 rs1695, as well as GSTM1 and GSTT1 genes, among workers in occupational settings - Sosan Andleeb Khan; Syed Muhammad Nurulain; Rashid Nazir Qureshi; Amina Zafar; Zarish Riaz; Aneela Shoukat; Zahid Muneer; Nazia Bibi; Saqlain Raza; Sabir Hussain; Syed Tahir Abbas Shah (Environmental Toxicology and Pharmacology, 2024)

Correction: Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Pakistan’s circular bio-economy: potential, opportunities and sustainable development - Yousaf Ali; Muhammad Sabir; Saad Afridi; Zahid Ullah (Environment, Development and Sustainability, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Horticulture crop under pressure: Unraveling the impact of climate change on nutrition and fruit cracking - Muhammad Aamir Manzoor; Yan Xu; Zhengxin lv; Jieming Xu; Iftikhar Hussain Shah; Irfan Ali Sabir; Yuxuan Wang; Wanxia Sun; Xunju Liu; Li Wang; Ruie Liu; Songtao Jiu; et al. (Journal of Environmental Management, 2024)

Mapping the low tolerance factor Bi(Li1/3Zr2/3)O3 end member and MPB composition nexus in Bi1/2Na1/2TiO3-based ceramics - Sabir Ali; Muhammad Sheeraz; Aman Ullah; Won Seok Yun; Amir Ullah; Ill Won Kim; Chang Won Ahn (Chemical Engineering Journal, 2024)

Sublethal impacts of Buprofezin and Pyriproxyfen on cotton mealybug Phenacoccus solenopsis through transgenerational hormesis - Sabir Hussain; Khalid Ali Khan; Muhammad Rafiq Shahid; Tooba Ather; Lal Khan; Amna Bibi; Sadia Kanwal; Nadia Hussain Ahmad; Ali Jan Bugti (Phytoparasitica, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Co-application of biochar and salt tolerant PGPR to improve soil quality and wheat production in a naturally saline soil - Laraib Malik; Muhammad Sanaullah; Faisal Mahmood; Sabir Hussain; Tanvir Shahzad (Rhizosphere, 2024)

First report on genotypic estimation of MRSA load in udder of nomadic sheep flocks affected with subclinical mastitis in Pakistan - Muhammad Jawad Sabir; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Muhammad Umar Javed; Farwa Anwaar (Research in Veterinary Science, 2024)

Handling the mishandling: Resolving the resource curse through effective utilization of available natural resources and claiming sustainable development - Ruijuan Qi; Ali Junaid Khan; Muhammad Farhan Basheer; Waseem Ul Hameed; Iffat Sabir Chaudhry (Resources Policy, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

An Integrated Approach for Biodegradation of Toxic Azo Dyes and Wastewater Recycling by Azoreductase Gene–Harboring Bacillus paramycoides Strain AM-3 - Awais Maqsood; Khola Tazeen; Sabir Hussain; Faisal Mahmood; Muhammad Shahid (Water, Air, & Soil Pollution, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Circular economy and its implementation in cement industry: A case point in Pakistan - Azfar Uddin; Yousaf Ali; Muhammad Sabir; Antonella Petrillo; Fabio De Felice (Science of The Total Environment, 2023)

Environmental implications of phosphate-based fertilizer industrial waste and its management practices - Noman Ahmad; Muhammad Usman; Hamaad Raza Ahmad; Muhammad Sabir; Zia Ur Rahman Farooqi; Muhammad Tahir Shehzad (Environmental Monitoring and Assessment, 2023)

Cotton and drought stress: An updated overview for improving stress tolerance - Sadia Zafar; Hadiqa Afzal; Areeba Ijaz; Athar Mahmood; Atif Ayub; Airish Nayab; Sadam Hussain; Maqsood UL-Hussan; Muhammad Azeem Sabir; Usman Zulfiqar; Faisal Zulfiqar; Anam Moosa (South African Journal of Botany, 2023)

Chronic exposure to electronic waste poses risk to liver toxicity with molecular interaction of GSTM1, GSTT1 null variants, and GSTP1 - Aneela Shoukat; Syed Muhammad Nurulain; Sabir Hussain; Sosan Andleeb Khan; Hussain Ahmed; Zahid Muneer; Syed Tahir Abbas Shah; Saqlain Raza; Syed Ali Musstjab Shah Eqani (Environmental Pollution, 2023)

Co-application of copper oxide nanoparticles and Trichoderma harzianum with physiological, enzymatic and ultrastructural responses for the mitigation of salt stress - Iftikhar Hussain Shah; Irfan Ali Sabir; Asad Rehman; Muhammad Khalid Hameed; Gadah Albashar; Muhammad Aamir Manzoor; Awais Shakoor (Chemosphere, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Environmental sustainable: Biogenic copper oxide nanoparticles as nano-pesticides for investigating bioactivities against phytopathogens - Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Irfan Ali Sabir; Ajaz Ahmad; Gadah Albasher; Afzal Ahmed Dar; Muhammad Ahsan Altaf; Awais Shakoor (Environmental Research, 2023)

Evidence and Molecular Characterization of Multidrug Resistant Staphylococcus aureus Isolated From Equines in Pakistan - Farwa Anwaar; Muhammad Ijaz; Hamza Rasheed; Syed Faizan Ali Shah; Syed Ali Raza Haider; Muhammad Jawad Sabir (Journal of Equine Veterinary Science, 2023)

A causal link between financialization and ecological status: a novel framework for Asian countries? - Saeed Ahmad Sabir; Mubeen Abdur Rehman; Muhammad Zahid Javed; Usman Mehmood; Rabia Ishaq (Environmental Science and Pollution Research, 2023)

Differential response of nano zinc sulphate with other conventional sources of Zn in mitigating salinity stress in rice grown on saline-sodic soil - Rubaz Ahmed; Muhammad Zia-ur-Rehman; Muhammad Sabir; Muhammad Usman; Muhammad Rizwan; Zahoor Ahmad; Hesham F. Alharby; Hassan S. Al-Zahrani; Hameed Alsamadany; Amal Y. Aldhebiani; Yahya M. Alzahrani; Atif A. Bamagoos (Chemosphere, 2023)

Combined Effect of Rice-Straw Biochar and Humic Acid on Growth, Antioxidative Capacity, and Ion Uptake in Maize (Zea mays L.) Grown Under Saline Soil Conditions - Zaffar Malik; Natasha Malik; Iqra Noor; Muhammad Kamran; Aasma Parveen; Muhammad Ali; Freeha Sabir; Hosam O. Elansary; Tarek K. Zin El-Abedin; Eman A. Mahmoud; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Prevalence and abundance of antibiotic-resistant genes in culturable bacteria inhabiting a non-polar passu glacier, karakorum mountains range, Pakistan - Sabir Nawaz; Muhammad Rafiq; Ian L. Pepper; Walter Q. Betancourt; Aamer Ali Shah; Fariha Hasan (World Journal of Microbiology and Biotechnology, 2023)

Dysregulation of butyrylcholinesterase, BCHE gene SNP rs1803274, and pro-inflammatory cytokines in occupational workers - Sosan Andleeb Khan; Mbah Ntepe Leonel Javeres; Syed Tahir Abbas Shah; Nazia Bibi; Zahid Muneer; Sabir Hussain; Eugenie Nepovimova; Kamil Kuca; Syed Muhammad Nurulain (Environmental Research, 2023)

Phytotoxic effects of chemically synthesized copper oxide nanoparticles induce physiological, biochemical, and ultrastructural changes in Cucumis melo - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fiza Liaquat; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Science and Pollution Research, 2023)

Stochastic procedures to solve the nonlinear mass and heat transfer model of Williamson nanofluid past over a stretching sheet - Thongchai Botmart; Zulqurnain Sabir; Muhammad Asif Zahoor Raja; Wajaree weera; R. Sadat; Mohamed R. Ali (Annals of Nuclear Energy, 2023)

Evaluating adoption of climate smart agricultural practices among farmers in the Fujian Province, China - Rao Sabir Sattar; Muhammad Sajid Mehmood; Muhammad Hammad Raza; V. P. I. S. Wijeratne; Babar Shahbaz (Environmental Science and Pollution Research, 2023)

Application of silver nanoparticles synthesized through varying biogenic and chemical methods for wastewater treatment and health aspects - Asima Rasheed; Sabir Hussain; Waseem Mushtaq; Muhammad Zubair; Khadija Siddique; Kotb Attia; Naeem Khan; Sajid Fiaz; Farrukh Azeem; Yinglong Chen (Environmental Science and Pollution Research, 2023)

A green and environmental sustainable approach to synthesis the Mn oxide nanomaterial from Punica granatum leaf extracts and its in vitro biological applications - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Shazma Gulzar; Liying Chang; Yidong Zhang (Environmental Monitoring and Assessment, 2022)

Impact of Water Regimes on Minimizing the Accumulation of Arsenic in Rice (Oryza sativa L.) - Muhammad Tahir Shehzad; Muhammad Sabir; Saifullah; Abu Bakkar Siddique; Mohammad Mahmudur Rahman; Ravi Naidu (Water, Air, & Soil Pollution, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Apportionment of heavy metals in a soil–water-plant system via brick kiln emissions in heavily industrialized city of Pakistan - Imran Ahmad; Hamaad Raza Ahmad; Zia Ur Rahman Farooqi; Muhammad Sabir; Muhammad Rizwan; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2022)

Phytochemicals targeting NAFLD through modulating the dual function of forkhead box O1 (FOXO1) transcription factor signaling pathways - Usman Sabir; Hafiz Muhammad Irfan; Alamgeer; Ihtisham Umer; Zahid Rasul Niazi; Hafiz Muhammad Mazhar Asjad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Arsenic concentrations in soil, water, and rice grains of rice-growing areas of Punjab, Pakistan: multivariate statistical analysis - Muhammad Tahir Shehzad; Muhammad Sabir; Muhammad Zia-ur-Rehman; Muhammad Anjum Zia; Ravi Naidu (Environmental Monitoring and Assessment, 2022)

Do neonicotinoids better than pyrethroids for Coccinella septempunctata L. (Coleoptera: Coccinellidae)? A comparative sub-lethal indirect age-stage, two-sex life tables laboratory bioassay - Muhammad Rizwan; Bilal Atta; Misbah Rizwan; Ijaz Ashraf; Muhammad Arshad; Muhammad Tahir; Mudassir Ali; Arshed Makhdoom Sabir; Muhammad Bilal; Muhammad Yasir Ali (International Journal of Tropical Insect Science, 2021)

Foliar Spray of Natural and Synthetic Plant Growth Promoters Accelerates Growth and Yield of Cotton by Modulating Photosynthetic Pigments - Muhammad Shaukat; Ashfaq Ahmad; Tasneem Khaliq; Irfan Afzal; Sher Muhammad; Bushra Safdar; Sabir Hussain Shah (International Journal of Plant Production, 2021)

Comparative Effect of Fertilization Practices on Soil Microbial Diversity and Activity: An Overview - Muhammad Shehryar Sabir; Farah Shahzadi; Farooq Ali; Qismat Shakeela; Zeeshan Niaz; Shehzad Ahmed (Current Microbiology, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Biostratigraphic investigation and depositional model of the Late Thanetian Ranikot and the Ypresian Laki formations in the subsurface of the Southern Indus Basin, Pakistan - Hussain Asghar; Muhammad Saleem Mughal; Muhammad Sabir Khan; Saeed Abbas; Muhammad Hanif; Gulfam Hussain; Muhammad Ali; Kazim Ali; Amjad Hussain (Arabian Journal of Geosciences, 2021)

Environmental quality and output volatility: the case of South Asian economies - Muhammad Tariq Majeed; Maria Mazhar; Samina Sabir (Environmental Science and Pollution Research, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

Surface water quality assessment of Skardu springs using Water Quality Index - Wazir Aitizaz Ahsan; Hamaad Raza Ahmad; Zia Ur Rahman Farooqi; Muhammad Sabir; Muhammad Ashar Ayub; Muhammad Rizwan; Predrag Ilic (Environmental Science and Pollution Research, 2021)

Effect of plant spacing on incidence of rice planthoppers in transplanted rice crop - Muhammad Asghar; Talfoor-ul Hassan; Muhammad Arshad; Asif Aziz; Muhammad Tahir Latif; Arshed Makhdoom Sabir (International Journal of Tropical Insect Science, 2021)

Lethal and sublethal effects of clothianidin, imidacloprid and sulfoxaflor on the wheat aphid, Schizaphis graminum (Hemiptera: Aphididae) and its coccinellid predator, Coccinella septempunctata - Bilal Atta; Muhammad Rizwan; Arshed Makhdoom Sabir; Muhammad Dildar Gogi; Muhammad Asif Farooq; Abdullah Jamal (International Journal of Tropical Insect Science, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Comparative Response of Two Rice (Oryza sativa L.) Cultivars to Applied Zinc and Manganese for Mitigation of Salt Stress - Faisal Nadeem; Muhammad Azhar; Muhammad Anwar-ul-Haq; Muhammad Sabir; Tayyaba Samreen; Abdullah Tufail; Hafiz Umair Masood Awan; Wu Juan (Journal of Soil Science and Plant Nutrition, 2020)

Structural changes in carbon dioxide (CO2) emissions in the United Kingdom (UK): an emission multiplier product matrix (EMPM) approach - Yousaf Ali; Rosita Pretaroli; Muhammad Sabir; Claudio Socci; Francesca Severini (Mitigation and Adaptation Strategies for Global Change, 2020)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

Green remediation of saline–sodic Pb-factored soil by growing salt-tolerant rice cultivar along with soil applied inorganic amendments - Muhammad Mazhar Iqbal; Tayyaba Naz; Mazhar Iqbal Zafar; Muhammad Imtiaz; Omer Farooq; Atique ur Rehman; Shafaqat Ali; Muhammad Rizwan; Sabir Hussain; Wasim Javed; Ghulam Murtaza; Muhammad Afzal; et al. (Paddy and Water Environment, 2020)

Application of a Dye-Decolorizing Pseudomonas aeruginosa Strain ZM130 for Remediation of Textile Wastewaters in Aerobic/Anaerobic Sequential Batch Bioreactor and Soil Columns - Zahid Maqbool; Muhammad Shahid; Farrukh Azeem; Tanvir Shahzad; Faisal Mahmood; Muzammal Rehman; Tanvir Ahmed; Muhammad Imran; Sabir Hussain (Water, Air, & Soil Pollution, 2020)

Human exposure to bisphenol A through dietary sources and development of diabetes mellitus: a cross-sectional study in Pakistani population - Muhammad Ejaz Ul Haq; Muhammad Sajid Hamid Akash; Shakila Sabir; Malik Hassan Mahmood; Kanwal Rehman (Environmental Science and Pollution Research, 2020)

Diabetes-associated infections: development of antimicrobial resistance and possible treatment strategies - Muhammad Sajid Hamid Akash; Kanwal Rehman; Fareeha Fiayyaz; Shakila Sabir; Mohsin Khurshid (Archives of Microbiology, 2020)

Water resources and tourism development in South Asia: an application of dynamic common correlated effect (DCCE) model - Muhammad Saeed Meo; Saeed Ahmad Sabir; Hira Arain; Raima Nazar (Environmental Science and Pollution Research, 2020)

Damage potential of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) on wheat grains stored in hermetic and non-hermetic storage bags - Bilal Atta; Muhammad Rizwan; Arshed Makhdoom Sabir; Muhammad Dildar Gogi; Kazam Ali (International Journal of Tropical Insect Science, 2020)

Assessment of noise pollution and its effects on human health in industrial hub of Pakistan - Zia Ur Rahman Farooqi; Muhammad Sabir; Junaid Latif; Zubair Aslam; Hamaad Raza Ahmad; Iftikhar Ahmad; Muhammad Imran; Predrag Ilić (Environmental Science and Pollution Research, 2020)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Geochemical attributes of late Neoproterozoic Salt Range Formation, Pakistan: constraints on provenance, paleoclimate, depositional and tectonic settings - Muhammad Ahmed Farooqui; Muhammad Umar; Muhammad Amjad Sabir; Rashid Pervez; Tarib Jalees (Geosciences Journal, 2019)

An empirical investigation of the determinants of CO2 emissions: evidence from Pakistan - Imran Khan; Neelofar Khan; Asim Yaqub; Muhammad Sabir (Environmental Science and Pollution Research, 2019)

Assessment of trace elements in urban topsoils of Rawalpindi-Pakistan: a principal component analysis approach - Muhammad Tahir Shehzad; Ghulam Murtaza; Muhammad Shafeeque; Muhammad Sabir; Haq Nawaz; Muhammad Jamal Khan (Environmental Monitoring and Assessment, 2019)

Endocrine disruption as an adverse effect of non-endocrine targeting pharmaceuticals - Shakila Sabir; Muhammad Furqan Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2019)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Determination of the role of salicylic acid and Benzothiadiazole on physico-chemical alterations caused by Cucumber mosaic virus in tomato - Rana M. Sabir Tariq; Khalid P. Akhtar; Amjad Hameed; Najeeb Ullah; Muhammad Y. Saleem; Imran ul Haq (European Journal of Plant Pathology, 2018)

Petrography, provenance, diaganesis and depositional environment of Murree Formation in Jhelum Valley, Sub Himalayas, Azad Jammu and Kashmir, Pakistan - Muhammad Zaheer; Muhammad Sabir Khan; Muhammad Saleem Mughal; Noman Abbasi (Arabian Journal of Geosciences, 2017)

Contrasting Effects of Organic and Inorganic Amendments on Reducing Lead Toxicity in Wheat - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Sabir; Muhammad I. Sohail (Bulletin of Environmental Contamination and Toxicology, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Characterization of a salt resistant bacterial strain Proteus sp. NA6 capable of decolorizing reactive dyes in presence of multi-metal stress - Naila Abbas; Sabir Hussain; Farrukh Azeem; Tanvir Shahzad; Sajjad Haider Bhatti; Muhammad Imran; Zulfiqar Ahmad; Zahid Maqbool; Muhammad Abid (World Journal of Microbiology and Biotechnology, 2016)

Computing soil creep velocity using dendrochronology - Mohammad Amjad Sabir; Muhammad Umar; Muhammad Farooq; Faridullah Faridullah (Bulletin of Engineering Geology and the Environment, 2016)

Perspectives of using fungi as bioresource for bioremediation of pesticides in the environment: a critical review - Zahid Maqbool; Sabir Hussain; Muhammad Imran; Faisal Mahmood; Tanvir Shahzad; Zulfiqar Ahmed; Farrukh Azeem; Saima Muzammil (Environmental Science and Pollution Research, 2016)

Use of RSM modeling for optimizing decolorization of simulated textile wastewater by Pseudomonas aeruginosa strain ZM130 capable of simultaneous removal of reactive dyes and hexavalent chromium - Zahid Maqbool; Sabir Hussain; Tanvir Ahmad; Habibullah Nadeem; Muhammad Imran; Azeem Khalid; Muhammad Abid; Fabrice Martin-Laurent (Environmental Science and Pollution Research, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Comparative efficacy of ANN and ANFIS models in estimating biosurfactant production produced by Klebseilla sp. FKOD36 - Zulfiqar Ahmad; Muhammad Arshad; David Crowley; Benyamin Khoshnevisan; Marziye Yousefi; Muhammad Imran; Sabir Hussain (Stochastic Environmental Research and Risk Assessment, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Effect of inorganic amendments for in situ stabilization of cadmium in contaminated soils and its phyto-availability to wheat and rice under rotation - Muhammad Zia-ur Rehman; Muhammad Rizwan; Abdul Ghafoor; Asif Naeem; Shafaqat Ali; Muhammad Sabir; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2015)

Abiotic and Biotic Processes Governing the Fate of Phenylurea Herbicides in Soils: A Review - Sabir Hussain; Muhammad Arshad; Dirk Springael; Sebastian R. SøRensen; Gary D. Bending; Marion Devers-Lamrani; Zahid Maqbool; Fabrice Martin-Laurent (Critical Reviews in Environmental Science and Technology, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Microbial biotechnology for decolorization of textile wastewaters - Muhammad Imran; David E. Crowley; Azeem Khalid; Sabir Hussain; Muhammad Waseem Mumtaz; Muhammad Arshad (Reviews in Environmental Science and Bio/Technology, 2015)

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Characterization of Reactive Red-120 Decolorizing Bacterial Strain Acinetobacter junii FA10 Capable of Simultaneous Removal of Azo Dyes and Hexavalent Chromium - Faiza Anwar; Sabir Hussain; Shahla Ramzan; Farhan Hafeez; Muhammad Arshad; Muhammad Imran; Zahid Maqbool; Naila Abbas (Water, Air, & Soil Pollution, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Mechanisms of metal-phosphates formation in the rhizosphere soils of pea and tomato: environmental and sanitary consequences - Annabelle Austruy; Muhammad Shahid; Tiantian Xiong; Maryse Castrec; Virginie Payre; Nabeel Khan Niazi; Muhammad Sabir; Camille Dumat (Journal of Soils and Sediments, 2014)

Rb1/105 gene alterations and head and neck carcinogenesis - Maimoona Sabir; Ruqia Mehmood Baig; Ishrat Mahjabeen; Muhammad Saeed; Faraz Arshad Malik; Mahmood Akhtar Kayani (Molecular Biology Reports, 2012)